Stabilitas Obat dalam Pengembangan Produk Farmasi: Tinjauan Berdasarkan Pedoman International Council for Harmonisation (ICH) - Indah br Harahap; Ike Maharani; Lirayu Sitompul; Melda Febriayana Hasibuan; Rafiah Nasution; Selvia Nurdea Syahfitri; Cory Linda Futri Hrp (Journal of Medical Practice and Research, 2026)
Drug stability is a critical parameter in pharmaceutical product development that determines quality, safety, and efficacy throughout the product life cycle. This study aims to analyze the principles and application of stability studies based on the International Council for Harmonization guidelines in the context of formulation development, packaging, and shelf life determination. The method used is a non-empirical literature review of scientific articles published between 2010 and 2024 that are relevant to pharmaceutical stability and quality regulations. The analysis was conducted through a systematic selection process, conceptual data extraction, and comparative synthesis of long-term, accelerated, and intermediate stability test parameters in accordance with ICH standards. The results of the study show that the application of standardized stability study designs, the selection of representative storage conditions, and the periodic evaluation of physicochemical and microbiological changes play an important role in ensuring product quality consistency. The integration of a risk-based approach and validated documentation also improves regulatory compliance and product development efficiency. The harmonization of stability study practices based on ICH guidelines is a strategic foundation for ensuring the acceptance of pharmaceutical products in the global market and protecting patient safety. These findings support scientific decision-making in the registration and distribution process.